The Influence of Emotional Intelligence and Learning Environment on the Level of Understanding in Learning Mediated by Ability Among Management Students of the 2022 Cohort at Pelita Bangsa University - Azkia Khumairah; Putri Aprilliya; Retno Purwani Setyaningrum (Jurnal Manajemen Bisnis Eka Prasetya, 2025)
This study aims to analyze the impact of emotional intelligence and the learning environment on the level of learning comprehension, with ability serving as a mediating variable. The primary focus of this research is on the management students from the 2022 cohort at Pelita Bangsa University. In the digital era and online learning environment, achieving a deep understanding of course material has become a major challenge for students. It is believed that strong emotional intelligence and a supportive learning environment can enhance learning effectiveness and comprehension. This study uses a quantitative approach with a survey method, employing purposive sampling to select 117 respondents. Data was collected through a questionnaire that measured emotional intelligence, learning environment, ability, and learning comprehension. The results of hypothesis testing indicate that both emotional intelligence and the learning environment significantly influence learning comprehension through the mediation of ability. The findings offer valuable insights into how emotional and environmental factors, when supported by ability, can improve the quality of student learning at Pelita Bangsa University. This study also highlights the importance of developing students' adaptive abilities to enhance their understanding of material in the era of online learning.